The influence of impinging jets on hydraulic jumps - Yüksel, Y; Günal, M; Bostan, T; Çevik, E; Çelikoglu, Y (THOMAS TELFORD PUBLISHING, 2004)
Experiments were carried out in a horizontal channel with a free jump and jumps with jets introduced at various angles. Particles within the jumps were traced using a high-speed video camera and the images were processed using a computer to determine particle velocities within the jumps. A simple numerical model using Strip Integrals across the flow is used to predict the kinematic characteristics of such jumps. Numerical and experimental results agree satisfactorily. The results show that even a relatively small momentum flux of the impinging jet can profoundly influence the jump in terms of the velocities within the jump and its surface profile. Plunging breakers occurring on a beach as the wave breaks may also be represented as a hydraulic jump with a weak jet impinging at its toe. This study shows that the impinging jet can increase energy dissipation within a plunging breaker.
Keywords: coastal engineering; hydraulics & hydrodynamics; sea defences; Engineering; Water Resources